(untitled) (Historia, 2021)
In 1950, Africans residing on the Rhodesdale Estate were forcibly evicted from designated Crown Land under the Native Land Husbandry Act by the Rhodesian state and were resettled in the Sanyati communal lands, then known as "native reserves". Eviction and resettlement were part of the re-ordering of African agricultural settlement and development to pave the way for white settler farmers in the Rhodesdale Estate following white migration to Rhodesia in the aftermath of the First World War. This reorganisation was premised on modernisation theory. This article challenges the white-dominated state’s notion of modernisation by arguing that far from uplifting the lives of rural Africans, the state, using its racially-oriented legislative machinery, was not altruistic but aimed to turn Rhodesia into a "white man’s country" intolerant of African economic competition. Discriminatory legislation led to scuttling socio-economic differentiation and obstructing the emergence of an entrepreneurial class in Sanyati. By investigating the evictions and resettlement of people from 1950 to 1966, this article argues that alongside the grand theme of separate development adopted by the Rhodesian settler state, there was an equally significant theme of African economic struggle to resist their marginalisation and impoverishment. The article provides historical data on livelihoods, migration and the impact of legislation, and demonstrates that colonial legislation in Southern Rhodesia stimulated the white-dominated economy through state support. It further argues that the intersection between state-promoted agricultural development, land allocation and the legislative requirements directing or prescribing standards for the separate development of Africans and whites, not only illustrates the generic growth of Sanyati, but also the historic evolution of a largely cotton-based economy which stimulated significant forms of rural differentiation in this region.